Breastfeeding Empowerment Models for Young Mothers in Indonesia - Mufdlilah (International Journal of Advanced Science and Technology, 2020)
Breastfeeding the most important of a baby’s life. Breastfeeding is considered an important factor of empowerment in breastfeeding. Breastfeeding for young mothers creates various pressures and negative stigma. This can affect the mother in giving breast milk to her baby. The aim of this study is to find empowerment efforts in exclusive breastfeeding programs, especially for young mothers because of young mothers. This is a cross-sectional study. This study involved 300 young mothers breastfeeding in Gunungkidul District.Data collection using a questionnaire. Data analysis using SEM. Goodness of fit model tests, the structural model of breastfeeding empowerment in young mothers is fit according to empirical data. Chi square value is 611.41 < 2db, RMSEA is 0.047 ≤ 0.08, ECVI is 2.66 < 3.11 < 24.13, AIC is 803.41 < 930.00, CAIC 1254.98 < 3117.26, IFI is 0.96 < 0.80, and RFI is 0.89. The result show relationship between policy and advocation (5.61 >1.96), advocation with support (6.30 > 1.96), support with attitude (2.04 > 1.96), perception with participation (3.40 > 1.96), and participation with attitude (3.33 > 1.96). The breastfeeding empowerment model for young mothers fulfills all predetermined criteria. This model can be implemented as an effort to increase the awareness and attitude of mothers in exclusive breastfeeding.